Preterm birth rate and dilemma of preterm labor treatment in Asia. (April 2019) - Hoh, Jeong-Kyu; Lappas, Martha; Liu, Calixia; Qiao, Chong; Pallavi, Kshetrapal; Takeda, Jun; Kim, Young Ju
Highlights: The preterm birth rates (PTB) vary between Asian countries. Datasets from maternity services from each country are fundamental forunderstanding of the global burden For better prediction, treatment and prevention of PTB, rigorous studies towards molecular understanding of PTB is the need of the hour